Risk stratification and scoring systems in upper and lower gastrointestinal bleeding: review of performance and limitations in the emergency department - Mohammadyari, Fatemeh; Aflak, Amirreza; ZareDini, Mahta; Irandoost, Reza; Ghaffari, Saeed; Gharib, Arsham; Roshanaei, Minaalsadat; Tahavori, Mazyar; Olangian-Tehrani, Sepehr (Frontiers in Medicine, 2025)
BackgroundGastrointestinal bleeding (GIB), which includes both upper GIB (variceal and non-variceal) and lower GIB, represents a significant cause of emergency department referrals.Main bodyGiven the potential risks of blood transfusion, re-bleeding, and mortality in these patients, it is essential to establish a system for prioritizing critical patients. Several risk stratification scoring systems have been developed based on patients' clinical characteristics and/or endoscopic findings. However, the optimal scoring system for each clinical scenario remains uncertain.ConclusionIn this study, we design the first comprehensive review and compare almost all of the upper gastrointestinal bleeding (UGIB), as well as lower gastrointestinal bleeding (LGIB) risk stratification scoring systems individually regarding their advantages, disadvantages, and limitations.